Pengaruh Return On Equity, Kepemilikan Manajerial, Ukuran Perusahaan Terhadap Prudent Akuntansi - Budi Rohmansyah; Dede Soenaryo; Indra Gunawan Siregar (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
In presenting quality financial statements, companies are faced with considerations, one of which is the prudent principle of accounting. This study aims to examine and analyze related to ROE, company size and board size to the company's prudence in making financial statements or prudent accounting. The design of this study uses explanatory causality research design using Eviews 9. The population used in this study is a company engaged in the manufacturing sector, namely the textile and garment sector during the period 2010-2014. The results of this study indicate that partially only the ROE variable has a significant effect on prudent accounting. While managerial ownership and company size have no effect on prudent accounting. The findings in this study are the equalization of positions between agents and principals through share ownership by managers (agents) unable to improve the prudent application of accounting. And the company does not consider its size too much in applying prudent accounting.Keywords: ROE, Managerial ownership, firm size, prudent accounting